Impact of Government Policy on Women Empowerment: Evidence from the Poverty Alleviation Fund, Nepal - Gautam, Susmita (NUTA Journal, 2020)
Traditionally, most of the women in developing countries like Nepal have had to face different forms of inequality and discrimination such as limited access to education, deprivation from property rights and forced early marriage mainly due to the patriarchal structure of society. As a result, gender disparity, forced marriage and violence against them, women have a lower societal status and lower level of education, few accesses to employment and legal rights compared to male. Government policies and programs helps to improve all the aspects of women empowerment. The main objective is to study the impact of government policy based programme for women empowerment. The study demonstrates the role, responsibility, opportunity, and decision-making issues of women. Taking reference of PAF model for women empowerment members of community organizations (CO) involved were selected as a sample. Both qualitative and quantitative data were analyzed. The PAF model takes community demand driven approach and supports the formation of representative community organizations of the poor and helps them identify their own development priorities, needs and solutions. The findings revealed that the women are in the process of their empowerment. They need position help and support from the family, society, and country as well. For this, country should develop gender friendly policies and programs.